Nanotechnologies in Food and Agriculture 2015
DOI: 10.1007/978-3-319-14024-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles-Based Delivery Systems in Plant Genetic Transformation

Abstract: The production of transgenic plants is considered as a valuable tool in plant research and the technology is comprehensively useful in agricultural research. Gene transfer in plants is generally carried out by Agrobacterium sp., application of some chemicals, and physical techniques (electroporation, microprojectile, etc.). Now-a-days with better efficacy and stability, new methods for the gene transfer in plants are coming up. The advent of nanotechnology, the nanoparticles-based delivery systems for genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 173 publications
0
15
0
Order By: Relevance
“…These methods are better efficacy and have the stable integration as well as the rapid expression for the transgenic process using nanoparticles (Rai et al 2015;Khodakovskaya and Lahiani 2016;Shukla et al 2016;Pacheco and Buzea 2017). These nanoparticles could be conjugated with nucleic acid developing the methodology of gene transfer in plants and improving the efficacy, stability and accuracy of transgenic process making it less time-consuming (Burlaka et al 2015;Rai et al 2015;Elahian et al 2017). Therefore, it could be concluded that, the encapsulation of nanomaterials could be considered the best method in delivering different agro-chemicals or different agricultural active ingredients in more efficient manner.…”
Section: Nanocapsules For Efficient Delivery Agrochemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…These methods are better efficacy and have the stable integration as well as the rapid expression for the transgenic process using nanoparticles (Rai et al 2015;Khodakovskaya and Lahiani 2016;Shukla et al 2016;Pacheco and Buzea 2017). These nanoparticles could be conjugated with nucleic acid developing the methodology of gene transfer in plants and improving the efficacy, stability and accuracy of transgenic process making it less time-consuming (Burlaka et al 2015;Rai et al 2015;Elahian et al 2017). Therefore, it could be concluded that, the encapsulation of nanomaterials could be considered the best method in delivering different agro-chemicals or different agricultural active ingredients in more efficient manner.…”
Section: Nanocapsules For Efficient Delivery Agrochemicalsmentioning
confidence: 99%
“…On the other hand, there are many applications of nanobiotechnology in agricultural sector including nano-encapsulated fertilizers (Chhipa 2016;Chhipa and Joshi 2016;Dubey and Mailapalli 2016;Khan and Rizvi 2017;López-Valdez and Fernández-Luqueño 2018) and pesticides (Kah et al 2014;Chhipa 2016;Chhipa and Joshi 2016;Dubey and Mailapalli 2016;Khan and Rizvi 2017;Abd-Elsalam and Prasad 2018) as well as nanoparticles mediated genetic material delivery in plants (Hatami et al 2016;Siddiqi and Husen 2017a;Tripathi et al 2017a). Furthermore, some delivery of mesoporous nanoparticles mediated DNA and proteins in plants have been proved (Rai et al 2015;Chung et al 2016;Rajan et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses infecting H. perforatum (Kegler et al, 1999 ) and H. japonicum (Du et al, 2013 ) have been identified and characterized. Furthermore, nanoparticle mediated DNA delivery into plant cells is gaining momentum (Rai et al, 2015 ), which would also offer potential benefits in the genetic transformation of H. perforatum in the future.…”
Section: Future Perspectives and Strategies For H Perforatmentioning
confidence: 99%
“…There are many established gene-transfer methods including Agrobacterium-mediated transformation, viral vectors, microinjection, biolistic or particle bombardment, PEGpolyethylene glycol and electroporation [1][2][3][4][5]. These methods do have some or the other limitations and are less efficient [6][7][8][9]. Many reports are also available on the gene-transfer by bioactive beads (BAB)-mediated transformation [10][11][12].…”
Section: Introductionmentioning
confidence: 99%